- PENGARUH CURRENT RATIO DAN RETURN ON EQUITY TERHADAP RETURN SAHAM (Studi Empiris Pada Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia Periode 2017-2022) - Komala, Ratna =; Harahap, Muhammad Nasim (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to ascertain whether the current ratio and return on equity both partially and simultaneously affect stock returns. 28 state-owned businesses that were listed on the Indonesia Stock Exchange from 2017 to 2022 make up the study’s population. Nine businesses made up the purposive sampling approach sample for this investigation. Documentation technique is the method of data collection that is employed. Descriptive statistical analysis, classical assumption test, multiple linear regression analysis, determination coefficient test and hypothesis testing with t test and F test were all used in the data analysis. The results of this study indicate that individually the current ratio has no effect on stock returns and return on equity affects stock returns. Simultaneously stock returns and return on equity affect stock returns.